2011
DOI: 10.2337/db11-0176
|View full text |Cite
|
Sign up to set email alerts
|

Total Zinc Intake May Modify the Glucose-Raising Effect of a Zinc Transporter (SLC30A8) Variant

Abstract: OBJECTIVEMany genetic variants have been associated with glucose homeostasis and type 2 diabetes in genome-wide association studies. Zinc is an essential micronutrient that is important for β-cell function and glucose homeostasis. We tested the hypothesis that zinc intake could influence the glucose-raising effect of specific variants.RESEARCH DESIGN AND METHODSWe conducted a 14-cohort meta-analysis to assess the interaction of 20 genetic variants known to be related to glycemic traits and zinc metabolism with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 48 publications
3
59
2
Order By: Relevance
“…The effects on the diabetic phenotype vary but globally, scientists observed beneficial effects especially in decreasing HbA1c levels and cholesterol. However, it is still unclear if dietary zinc supplementation would have an effect in preventing the disease in adults with insulino-resistance [17], and it has been shown recently that supplementation may affect the insulin response differentially, depending on the patient genotype for the SLC30A8 gene encoding the zinc transporter ZnT8 [18,19] (see below).…”
Section: Zinc and The Diabetic Patientmentioning
confidence: 99%
“…The effects on the diabetic phenotype vary but globally, scientists observed beneficial effects especially in decreasing HbA1c levels and cholesterol. However, it is still unclear if dietary zinc supplementation would have an effect in preventing the disease in adults with insulino-resistance [17], and it has been shown recently that supplementation may affect the insulin response differentially, depending on the patient genotype for the SLC30A8 gene encoding the zinc transporter ZnT8 [18,19] (see below).…”
Section: Zinc and The Diabetic Patientmentioning
confidence: 99%
“…(64)(65)(66)(67)(68) . Interestingly, the effects of dietary zinc supplementation to lower T2D risk are dependent on SLC30A8 genotype (69) . More recent studies in human populations have reported twelve rare loss-of-function SNP, resulting in the production of a truncated protein that is associated with a 65 % decrease in T2D risk (70) .…”
Section: +mentioning
confidence: 99%
“…SLC30A8 (the zinc transporter-8 gene) has been suggested as an interesting candidate for studying the interaction with total zinc intake and fasting glucose levels in individuals without T2D (15). SLC30A8 is almost exclusively expressed in pancreatic b-cells and encodes a protein that transports zinc from the cytoplasm into insulin secretory vesicles, an important step in insulin synthesis and secretion (16).…”
Section: Interactions Between Zinc Transporter-8 Gene (Slc30a8) and Pmentioning
confidence: 99%